Analysis of the Selling Price of Palm Sap Brown Sugar Using the Plus Cost Price Method in Pegajahan District - Syafira, Dinda; Daulay, Aqwa Naser; Aslami, Nuri (Yayasan Ilomata, 2025)
This study aims to analyze the selling price of palm sap brown sugar in Pegajahan District using the plus cost price method. Palm sap brown sugar is a processed product that has high economic value and is in great demand by the public, both for direct consumption and as an industrial raw material. However, selling prices that often fluctuate are a challenge for producers in determining reasonable and profitable prices. This study identifies the costs involved in the production process of palm sap brown sugar, such as raw material costs, labor, and other costs, as well as determining the feasible profit margin to set the selling price of the product. The cost plus price method is used to calculate the selling price by adding the corresponding profit margin to the total cost of production. The results of this study are expected to provide useful recommendations for palm sap brown sugar producers in Pegajahan District in determining the optimal selling price, as well as contributing to local economic development. In addition, this study also provides insight into the cost efficiency in palm sap brown sugar production in the area.